Role of grain boundaries in tailoring electronic properties of polycrystalline graphene by chemical functionalization. (6th May 2015) - Seifert, Max; Vargas, Jose E B; Bobinger, Marco; Sachsenhauser, Matthias; Cummings, Aron W; Roche, Stephan; Garrido, Jose A
Abstract: Grain boundaries, inevitably present in chemical vapor deposited graphene, are expected to have considerable impact on the development of graphene-based hybrid materials with tailored material properties. We demonstrate here the critical role of polycrystallinity on the chemical functionalization of graphene comparing ozone-induced oxidation with remote plasma hydrogenation. We show that graphene oxidation and hydrogenation occur in two consecutive stages upon increasing defect density: an initial step in which surface-bound functional groups are generated, followed by the creation of vacancies. Remarkably, we find that hydrogenation yields homogeneously distributed defects while ozone-induced defects are preferentially accumulated at the grain boundaries eventually provoking local cracking of the structure. Supported by quantum simulations, our experimental findings reveal distinct electronic transport regimes depending on the density and distribution of induced defects on the polycrystalline graphene films. Our findings highlight the key role played by grain boundaries during graphene functionalization, and at the same time provide a novel perspective to tailor the properties of polycrystalline graphene.